P3P semantic checker of site behaviours - Grande, Robson Eduardo (2006)
The interactive use of the web between users and service providers introduces a privacy problem that involves the undesired disclosing of user personal information, mainly with the presence of personalization that needs this type of information. Also there are many manners to face it, but the Platform for Privacy Preferences (P3P) is one that provides a variable level of privacy for the user’s browsing. However, the P3P only introduces a privacy contract between the site and the user, without guarantees that it will be obeyed by the site. Then a semantic checker can be added to the P3P architecture to compare the contract with the site attitude and to increase the trustworthiness on the P3P contract. Some experiments are accomplished and the results are displayed to show the present situation of the privacy policies of the sites, and we discuss what it implies in the data gathering and what is gained with the use of the semantic checker.